Pengambilan Keputusan Dalam Pemilihan Tempat Peletakan Alat di Laboratorium Teknik Industri Berdasarkan Keterbatasan Ruang dengan Metode AHP - Tri Aji Wicaksono; Andhika Mayasari; Sulung Rahmawan Wira Ghani (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2023)
Industrial engineering laboratory is an important component in a high-level learning in industrial engineering study program. The university wants a correct and proper layout for the placement of various kinds of learning support tools and practicums in the laboratory for Industrial Engineering students. There are 3 laboratory rooms, namely the Manufacturing Industry Laboratory, the Service Industry Laboratory, and the Industrial Integration System Laboratory. The research focused on the placement of laboratory equipment within the limited space available. This study aims to determine the priority criteria and alternative placement of the best laboratory equipment. The method used is AHP-TOPSIS, the AHP method is used for weighting the assessment criteria, while the TOPSIS method is used to sort the location of various laboratory equipment. The researcher determined that there were 4 criteria, namely the dimensions of the tool, the level of danger, maintenance, and the mobility of the tool. The conclusion that can be drawn is that the AHP-TOPSIS method can be used as a decision-making framework in selecting the right place for laying various laboratory equipment. Placement of tools that have the criteria of tool dimensions with heavy mass and mobility of tools that are often moved are placed in the Manufacturing Industry Laboratory.AHP, TOPSIS, laboratory, decision making